IMPLEMENTASI PROGRAM TAHFIDZ AL QUR'AN DI PONDOK PESANTREN SALAFIYAH IQRO PALANGKA RAYA - Mesyi, Mesyi; Dakir, Dakir; Riyadi, Slamet (Jurnal Manajemen Pendidikan, 2025)
Amidst the increasing need to strengthen religious education, the Al-Qur'an memorization program has become an important part in fostering a generation that is close to the Qur'an while also forming a religious character. Islamic educational institutions are required to have a structured tahfidz program management to be able to maintain the quality of memorization, discipline, and spiritual development of students. This study aims to describe the implementation of the Al-Qur'an memorization program at the Salafiyah Iqro Palangka Raya Islamic Boarding School which includes planning, implementation, and evaluation of learning. The study used a qualitative approach with observation, interview, and documentation techniques. The results showed that the boarding school implemented three main methods of sabaq, sabqi, and murajaah which were proven effective in improving the quality of memorization and maintaining long-standing memorization consistently. Memorization deposits were carried out three times a day, while routine evaluations were carried out through reports from female teachers regarding memorization achievements, discipline, and student motivation. This program not only produces strong and measurable memorization, but also plays a role in shaping the character of students who are religious, disciplined, and have good morals. Overall, the implementation of the tahfidz program at this Islamic boarding school is running effectively and in line with the principles of Islamic education management.